Evaluation of Robotics Education Program among Private Secondary Schools in Region IV-A CALABARZON - Santiago, Jan Michael; Naval , Victoria (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the implementation status of the Robotics Education Program among private secondary schools in Region IV-A CALABARZON and developed inputs for a program improvement plan. Guided by the CIPP (Context, Input, Process, Product) evaluation model, a descriptive evaluation research design and quantitative approach were used. Data were gathered from 130 robotics teacher-respondents from 40 selected private secondary schools in Cavite, Laguna, Batangas, and Rizal through a validated and reliability-tested researcher-made questionnaire. Data analysis employed frequency, percentage, and weighted mean, and examined group differences using Mann–Whitney U and Kruskal–Wallis tests. Results indicated that curriculum implementation was rated to a very large extent, while learning outcomes were rated to a large extent, with robotics perceived to strengthen critical thinking and problem-solving. Support services for professional development were generally utilized to a large extent, and teachers were very much interested in further training, particularly on robotics pedagogy and programming. Required robotics technologies were rated adequate overall, and access to electronic learning resources and common communication/programming tools was high. The leading implementation challenges were limited internet bandwidth, inadequate teacher robotics knowledge, and ICT network deficiencies. The study concluded that strengthening teacher capability and resourcing is necessary and recommended increased professional development, adequate budgeting for tools and licenses, stronger provider partnerships, broader participation opportunities, and potential integration into the national basic education curriculum. The study aligns with SDG 4 (Quality Education) and SDG 9 (Industry, Innovation and Infrastructure) by supporting evidence-based improvement of technology-enabled learning. Sustainability impact centers on educational and digital sustainability through strengthened capacity, infrastructure readiness, and institutional support for long-term program continuity.
Keywords: CIPP model; curriculum implementation; educational robotics; learning outcomes; private secondary schools; professional development; Robotics Education Program; training and development needs; technology-based learning resources